Remarks at the Spring Meetings 2020 Press Conference - Malpass, David (World Bank, Washington, DC, 2020)
David Malpass, President of the World Bank Group, spoke at the 2020 Spring meetings virtual press conference. He discussed the joint efforts of the IMF and the Bank in support of member countries, especially the poorest and most vulnerable. He reviewed how the G20 joint call focused upon a suspension in debt service payments to bilateral creditors during the crisis. The World Bank Group has taken fast, broad-based action in response to COVID-19. IDA, the part of the World Bank that makes grants and very concessional credits, will provide over fifty billion US dollars in new resources, and that IDA countries will have bilateral debt service relief beginning May 1, 2020. He warned of a major global recession, and how the World Bank Group is responding forcefully and massively, especially for the IDA countries, the poorest countries, involving significant increases in the highly concessional financing and grants. The International Finance Corporation is working very actively with companies to try to keep them open. The World Bank is looking for ways to do cash transfers through digital financial service systems. The World Bank also aim to aid governments to support small and medium-sized enterprises.